APPLICATION OF THE ARM'S LENGTH PRINCIPLE IN TRANSACTIONS RELATED TO INTANGIBLE ASSETS -PROBLEMS AND SOLUTION SUGGESTIONS- - ÇAMURCU, ZEYNEP NİHAN (MEHMET AKIF ERSOY UNIV, 2021)
Intangible assets, which are the product of the intellectual efforts of people, constitute a large part of the transfer pricing transactions today. Both the increasing use of the digital economy and the economic consequences of the scientific developments that have been increasing since the middle of the 19th century, cause the taxpayers (especially the multinational companies) who want to reduce the tax burden to realize the illegal behaviors that are the circumvention of the tax law. As a response to these behaviors, tax administrations are also trying to reach an economic reality in a comprehensive way. This situation makes the taxation process a difficult process to implement both for the taxpayers and the administration. The application of arm's length principle to transfer pricing transactions involving intangible assets has become a difficult structure for both tax administrations and taxpayers in today's world. In addition, the changes made with the Base Erosion and Profit Shifting project of the Organization for Economic Cooperation and Development regarding the definition of intangible assets that are the subject of royalti payments require the issue to be addressed in the light of current developments.
Keywords: Transfer Pricing; Related Parties; Royalti Price; Intangible Assets; Taxation